EFEKTIVITAS MODEL PEMBELAJARAN ICARE BERBASIS MEDIA AUTENTIK “BERBABE” TERHADAP HASIL BELAJAR BAHASA INGGRIS SISWA SEKOLAH DASAR - Maria Desidaria Noge (Jurnal Tunas Bangsa, 2017)
This research was important at finding out the significant difference between English learning achievements of students who were treated by using ICARE learning based authentic media “Berbabe” and students who were treated by using Conventional learning model of class V students in Jerebuu Catholic Primary School. This research was quasi experiment with Non Equivalent Control Group Design. The population of this research was class V students of Jerebuu Catholic Primary School totaled 40 students. The sample of research was class VA students as experiment group and class VB students as control group. Research data collected used English learning achievement instrument test formed objective test. The result of test next analyzed by using statistical trial t-test with counting Gane Score dinormalisasi (Gsn) from each group. The result of data analysis shows that there is significant difference of English learning achievement between students of experiment group and students of control group. It can be seen from the result of t-test analysis obtained that Tcount = 3,870 > Ttable = 2,042, (DB) = n1+ n2 – 2 = 38, significant level 5%. The average of English learning achievement in experiment group is higher than the average of English learning achievement in control group (0.50>0.38). Based on the results of research can be concluded that ICARE learning model based authentic media “Berbabe” is effectively used as English learning model for English teachers of Primary School so as to improve English learning achievement of Primary School students. Abstrak Penelitian ini penting dilakukan untuk mengetahui perbedaan yang signifikan antara hasil belajar bahasa Inggris siswa yang belajar melalui model pembelajaran ICARE berbasis media autentik “Berbabe” dengan siswa yang belajar menggunakan model pembelajaran Konvensional pada siswa kelas V SDK Jerebuu. Penelitian ini merupakan penelitian eksperimen semu (Quasi Experiment) dengan rancangan penelitian Non Equivalent Control Group Design. Populasi penelitian ini adalah siswa kelas V SDK Jerebuu berjumlah 40 orang. Sampel penelitian ini adalah siswa kelas VA sebagai kelompok eksperimen dan siswa kelas VB sebagai kelompok kontrol. Data penelitian dikumpulkan menggunakan instrumen tes hasil belajar bahasa Inggris berupa tes objektif. Hasil tes selanjutnya dianalisis dengan menggunakan pengujian statistik uji-t dengan menghitung Gane Score dinormalisasi (Gsn) dari setiap kelompok. Hasil analisis data menunjukkan bahwa terdapat perbedaan yang signifikan hasil belajar bahasa Inggris antara siswa kelompok eksperimen dan siswa kelompok kontrol. Hal ini dapat dilihat dari hasil analisis uji-t diperoleh bahwa Thitung = 3,870 > Ttabel = 2,042, (DB) = n1+ n2 – 2 = 38, taraf signifikan 5%. Rata-rata hasil belajar bahasa Inggris kelompok eksperimen lebih tinggi dari rata-rata hasil belajar kelompok kontrol (0,50>0,38). Berdasarkan hasil penelitian dapat disimpulkan bahwa model pembelajaran ICARE berbasis media autentik “Berbabe” efektif digunakan sebagai model pembelajaran bahasa Inggris bagi guru-guru bahasa Inggris SD sehingga dapat meningkatkan hasil belajar bahasa Inggris siswa Sekolah Dasar. Kata Kunci: Model Pembelajaran Icare, Media Autentik “Berbabe”, Sekolah Dasar